(untitled) (The Research of Medical Science Review, 2023)
Biomedical engineering is a multidisciplinary field that plays a crucial role in merging technological advancements and medical applications. This article explores the dynamic interface between technology and medicine through the lens of biomedical engineering, examining its evolution, current applications, and future prospects. By integrating engineering principles with biological and medical sciences, biomedical engineering has become a central force in revolutionizing healthcare, diagnostics and treatment modalities. This summary provides an overview of the main aspects covered in the article, providing insight into the interdisciplinary nature of biomedical engineering and its transformative impact on the healthcare landscape. Keywords: Biomedical engineering, Technology, Medicine, Interdisciplinarity, Health, Diagnosis, Treatment modalities, Evolution, Applications, Future perspectives.